Study on Physical and Thermal Properties of Edible Films from Modified Cassava Starch Incorporated with Zein Protein - Yokesahachart, Chanakorn; Chardchopowpong, Benjawan; Niramitmahapanja, Sarocha; Pajareon, Supaporn; Yokesahachart, Phasuchoke (Journal of Food Technology, Siam University, 2019)
Edible films are direct food contact materials i.e. thin films for food wrapping and film coating. Cassava starch is abundant in Thailand, cheap, it is often used as a raw material in food industry and film formability. However, edible films from cassava starch have some drawbacks such as poor mechanical properties and water sensitivity. Therefore, the properties of edible films from cassava starch have to be improved with different methods such as chemical modification of starch, and blending with hydrophobic polymers, etc. The present research studied preparation and properties of edible films from modified cassava starch with added zein protein by film casting using glycerol as a plasticizer. An unmodified cassava starch film with added zein protein was used as a control film. The results showed that modified cassava starch films with added zein protein were transparent, pale yellow and possess thickness in the range of 0.19–0.21 mm. The oxidized cassava starch film with added zein protein was homogenous, soft and flexible, whereas control film was stiff and strong. The cross-linked cassava starch film with added zein protein exhibited poor homogeneity of starch phase and protein phase, so its tensile properties and water absorption were inferior. Modification of cassava starch with oxidation gave good compatibility between cassava starch and zein protein.